2016
DOI: 10.25215/0302.056
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 20-Item Cultural Intelligence Scale in Indian within Country Migrated Students

Abstract: The objective of the present piece of work was to validation of 20 item cultural intelligence scale (CIS-20) in India within country migrated students. Following the incidental cum random sampling technique 200 North Indian engineering students within the age range of 18 to 24 years were drawn from different colleges of Warangal districts, Telangana, India to serve as participants in the present research work. The item analysis was done by corrected item-total correlation. The confirmatory factor analysis (CFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
4
5
0
Order By: Relevance
“…Furthermore, item loadings on the factors, that they belong to were greater than their loadings on other factors. These results are consistent with previous studies (Al-Dossary, 2016;Ang et al, 2007;Gozzoli & Gazzaroli, 2018;Khan & Hasan, 2016;Moyano et al, 2015;Şahin et al, 2013;Starčević et al, 2017), which is another supportive evidence of the construct validity for CQS with general and four specific factor structure, and the consistency of the relationships between CQS components across different cultures and countries. Moreover, this CTT-based evidence supported the CQS validity established by IRT-GRM in this study, which support relying on CQS full scale as well as subscales in assessing and interpreting CQ.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, item loadings on the factors, that they belong to were greater than their loadings on other factors. These results are consistent with previous studies (Al-Dossary, 2016;Ang et al, 2007;Gozzoli & Gazzaroli, 2018;Khan & Hasan, 2016;Moyano et al, 2015;Şahin et al, 2013;Starčević et al, 2017), which is another supportive evidence of the construct validity for CQS with general and four specific factor structure, and the consistency of the relationships between CQS components across different cultures and countries. Moreover, this CTT-based evidence supported the CQS validity established by IRT-GRM in this study, which support relying on CQS full scale as well as subscales in assessing and interpreting CQ.…”
Section: Discussionsupporting
confidence: 92%
“…for the scale) were similarly high for the CQS subscales and very high for the scale. These results based on CTT approaches agreed with previous studies(Al-Dossary, 2016;Ang et al, 2007;Barzykowski et al, 2019;Gozzoli & Gazzaroli, 2018;Greischel et al, 2021;Khan & Hasan, 2016;Moyano et al, 2015;Şahin et al, 2013;Starčević et al, 2017) that confirmed the evidence of high reliability of CQS full and subscales and subscales. In addition, subscales should be used as well as full scale based on purpose and expected person ability level.…”
supporting
confidence: 91%
See 3 more Smart Citations